Large ovarian mucinous cystadenoma in premenarchal girl: a case report - S., Pramod; Vani, Katragadda Satya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ovarian tumors are commonly seen in adults and rare in children. Incidence in children is about 2.6 cases per 1,00,000 girls. Most common ovarian mass in children is benign functional cyst. Epithelial tumors account for 8-10% of ovarian tumors. Most common epithelial tumor is Cystadenoma. Mucinous cystadenoma occurs in 3rd -6th decade of life. We report a 10-year-old Premenarchal girl presenting with abdominal distension and discomfort. On examination the entire abdomen was occupied by a firm mass. CT imaging showed a large multiloculated cystic lesion arising from the right ovary. The child underwent right salphingo-oophrectomy. The biopsy of mass was suggestive of benign mucinous cystadenoma. The child is on regular follow up. At 1 year follow up child is doing well.